INFLUENCE OF PRODUCT VALUE ON THE PERFORMANCE OF THE INSURANCE INDUSTRY IN KENYA - Ajwang, Benard Onyango; Ngugi, P. Karanja; Ogollah, Dr. Kennedy; Orwa, Dr. George (IJRDO - Journal of Business Management, 2016)
In view of firms financial prudence, firms see how best or poor they have achieved the set goals that existed in their Strategic reasoning. Financial prudence should be one of the fundamental factors taken into consideration by insurance companies before they venture either into any market or the launch of new products or services. A review on financial strategic intelligence plays a crucial role in the determination of whether a strategic plan is achieving the goals for which it was intended for and on whether programmes that were set to be accomplished are on track in terms of period and resource distribution. Insurance company Performance rating on the other hand provides a simplistic tool through which companies can strategically troubleshoot their position in terms of performance and how best they can work on their drawbacks as well as  continue improving on what they are doing best this is important especially in making financial related decisions.